2014
DOI: 10.5812/ircmj.9628
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Audiometry, Extended High-Frequency Audiometry, and DPOAE for Early Diagnosis of NIHL

Abstract: Background:Noise most frequently affects hearing system, as it may typically cause a bilateral, progressive sensorineural hearing loss at high frequencies.Objectives:This study was designed to compare three different methods to evaluate noise-induced hearing loss (conventional audiometry, high-frequency audiometry, and distortion product otoacoustic emission).Material and Methods:This was a cross-sectional study. Data was analyzed by SPSS (ver. 19) using chi square, T test and repeated measures analysis. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 22 publications
0
51
0
3
Order By: Relevance
“…The two most common tests are conventional audiometry, which tests thresholds in the 250-8,000 Hz range, and distortion product otoacoustic emissions (DPOAE) testing, which examines the function of OHCs. Although it is much less commonly used, extended high frequency audiometry, which tests the range from 8,000-16,000 Hz, can be useful in detecting early signs of hearing loss 78 .…”
Section: Audiogrammentioning
confidence: 99%
“…The two most common tests are conventional audiometry, which tests thresholds in the 250-8,000 Hz range, and distortion product otoacoustic emissions (DPOAE) testing, which examines the function of OHCs. Although it is much less commonly used, extended high frequency audiometry, which tests the range from 8,000-16,000 Hz, can be useful in detecting early signs of hearing loss 78 .…”
Section: Audiogrammentioning
confidence: 99%
“…Age-related hearing loss, noise-induced hearing loss (NIHL), and ototoxicity may be observed as a highfrequency hearing loss that gradually progresses toward lower frequencies (Durrant et al, 2009;Seddon et al, 2012;Mehrparvar et al, 2014). The acoustic energy of extended high frequencies (EHFs) plays an important role in speech perception, especially in the presence of background noise (Rodríguez Valiente et al, 2014;Vitela et al, 2014;Vlaming et al, 2014).…”
mentioning
confidence: 99%
“…[17,18] Somma et al [19] found high-frequency audiometry (10,000À16,000 Hz) to change earlier than conventional audiometry in noiseinduced hearing loss (500À6000 Hz). Mehrparvar et al [20] found that among three different methods (conventional audiometry, high-frequency audiometry and OAE) used for assessing noise-exposed workers, high-frequency audiometry is the most useful one. Extended high-frequency audiometry has been suggested as a method for monitoring the effects of noise exposure, ototoxic medication and hearing loss resulting from other causes.…”
Section: Resultsmentioning
confidence: 99%